1974
DOI: 10.1128/aac.6.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Concentrations of Benzylpenicillin on Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa produces a low basal level of β-lactamase (0.002 to 0.004 IU/mg of protein when benzylpenicillin is used as substrate). The β-lactamase specific activity can be increased several hundredfold by growing the bacteria in the presence of β-lactam antibiotics. This induction was studied in Pseudomonas aeruginosa 1822s. The single-cell resistance to benzylpenicillin was 750 μg/ml. In liquid culture all concentrations of benzylpenicillin tested (25 to 2,000 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…The result supports the findings of (Nordstrom & Sykes, 1973;Okonogi, Kuno,& Higashide, 1986;Raimondi, Sisto & Nikaido, 2007) who reported that the specific activity of β-lactamase increased linearly with increasing concentrations of inducer. In addition, Khan, Sallum, Zheng, Nau & Hassan (2014) in their study on rapid determination of β-lactamase and antibiotic activity detected β-lactamase in the absence of inducer however, at a lower level when compared with induction.…”
Section: Discussionsupporting
confidence: 81%
“…The result supports the findings of (Nordstrom & Sykes, 1973;Okonogi, Kuno,& Higashide, 1986;Raimondi, Sisto & Nikaido, 2007) who reported that the specific activity of β-lactamase increased linearly with increasing concentrations of inducer. In addition, Khan, Sallum, Zheng, Nau & Hassan (2014) in their study on rapid determination of β-lactamase and antibiotic activity detected β-lactamase in the absence of inducer however, at a lower level when compared with induction.…”
Section: Discussionsupporting
confidence: 81%
“…This conclusion is strenghtened by the fact that the lag before enzyme production starts is shorter the more inducer is added (26); at 4,000 ;&g of benzylpenicillin per ml the lag was only a few minutes (Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
“…This makes the induction of fl-lactamase a rather unphysiological response, since growth is greatly impaired by these high concentrations of antibiotic inducer (32). At nonlethal concentrations of inducer, the lag period before induction is more than a generation and is dependent on the concentration of inducer (26). Nonlethal concentrations of penicillin cause drastic changes in the functioning of the outer cell envelope (26).…”
mentioning
confidence: 99%
See 2 more Smart Citations